Transformational leadership style and innovative behavior with self-efficacy as a mediator - Sri Septriani (Human Resource Management Studies, 2021)
Purpose - This study aims to analyze: (1) The influence of transformational leadership style on innovative behavior on the employees of PT Samudra Distra Prima, Bukittinggi City, (2) The influence of transformational leadership style on self-efficacy on the employees of PT Samudra Distra Prima, Bukittinggi City, (3) The influence of self-efficacy on innovative behavior in PT Samudra Distra Prima Bukittinggi City employees, (4) The influence of transformational leadership style on innovative behavior with self-efficacy as a mediator in PT Samudra Distra Prima Bukittinggi City employees. Methodology - This type of research is a causative study. The population in this study were all employees of PT Samudra Distra Prima Bukittinggi City with 103 people. The sampling technique of this study was the Total Sampling technique or the entire population with a sample of 103 people. The data analysis technique used is multiple regression analysis with mediating variables with the SPSS Version 16.0 program. Finding - The results showed that: (1) Transformational leadership style had a positive and significant effect on innovative behavior on the employees of PT Samudra Distra Prima, Bukittinggi City, (2) Transformational leadership style had a positive and significant effect on self-efficacy on the employees of PT Samudra Distra Prima, Bukittinggi City, (3) Self-efficacy has a positive and significant effect on innovative behavior in PT Samudra Distra Prima Bukittinggi City employees, (4) Self-efficacy significantly mediates the relationship between transformational leadership style on innovative behavior in PT Samudra Distra Prima Bukittinggi City employees.